Correlation Between the Presences of Ascites with MELD-Na Scoring in Liver Cirrhosis Patients - Marcellus, Marcellus; Ratnasari, Neneng; Indrarti, Fahmi (Acta Interna The Journal of Internal Medicine, 2023)
Background. Global prevalence of liver cirrhosis (LC) ranges from 4.5% to 9.5% of the general population amounting to more than fifty million people in the world. The Model for End Stage Liver Disease (MELD-Na) is commonly used to determine the prognosis and survival of liver cirrhosis patient. MELD-Na scoring consists of creatinine, bilirubin, international normalized ratio (INR), and serum sodium. Ascites is one of the clinical signs of decompensated liver cirrhosis, as well as present in Child Turcotte Pugh (CTP). The purpose of this study was to investigate the association between the presence of ascites and MELD-Na scores of LC patients.Methods. This cross-sectional study was performed in LC patients who met the inclusion without exclusion criteria. The study was conducted at RSUP Dr. Sardjito, Yogyakarta, Indonesia during 2017-2018 periods. The MELD-Na value was calculated using the following equation:MELD-Na = 9.57 ln (creatinine mg/dL) + 11.2 ln (INR) + 3.78 ln (bilirubin mg/dL) + 1.59 (135-Na [mEq/L]) + 6.43. Differences of mean MELD-Na scores based on presenting of ascites were tested by independent T-tests. The cut-off value of MELD-Na was determined through the Receiver Operating Characteristic (ROC) curve. The relationship between the presence of ascites and the MELD-Na value was determined by the Fisher exact test; the correlation strength was determined by Phi and Crammer's V test. Prevalence ratio (PR) was calculated for determining the predictor factors. The results were considered statistically significant when the probability value p <0.05 was obtained.Results. There were 59 subjects (41 male and 18 female). The mean age of subjects was 52.05 years old. The 39 patients were found ascites and 20 patients were not. Based on independent T test results there was a significant difference in mean values of MELD-Na (p=0.006). Based on the ROC curve result, a cut-off point of 20.7 (95% specificity, 35% sensitivity) with Area under the Curve (AUC) was 0.662 (p=0.042). Based on the cut-off, Fisher test with 2x2 tables, Phi and Cramer's V test were done with p value 0.022; 0.015; 0.015 respectively. The PR value was 1.607 (95% CI: 1.203-2.145).Conclusion. There was a significant correlation between the presences of ascites with MELD-Na scoring using cut-off point of 20.7 and value of Prevalence Ratio of 1.6.